An Investigation of Optimum Safety Stock Level for Maintenance, Reliability and Operation Materials based on Criticality of Material and Equipment - Taufik Roni Sahroni; Bambang Sudjatmiko (International Journal of Supply Chain Management, 2018)
This paper presents a study to determine a safety stock level calculation for Maintenance, Reliability and Operation (MRO) materials in oil and gas industries. The challenge to set a safety stock for MRO materials is uncertainty of demand and lead time especially in industry where the operation plant is far away from materials manufacturer. Many models currently used to calculate the safety stock is independent between inventory control as service provider and maintenance as service receiver. Current models of safety stock are referred to equipment reliability or stock out situation to measure the effectiveness of the models. In this paper, studied the correlation between maintenance activities and inventory control strategy to provide acceptable service level thru combined equipment and material criticality with optimum inventory safety stock level by linked the acceptable downtime of equipment with lead time of ordering materials. Based on this study and comparison of the proposal with available models related to equipment and stock out focus, the proposal result is between current models of safety stock level calculation result